تصميم برنامج مسرحي لتنمية المهارات اللغوية لدى المعاقين سمعيا من تلاميذ الصف الرابع الأساسي في محافظة ظفار - محمد، عادل حسين على
This research aims to identify the effectiveness of a program based on the school stage and its impact on the development of language skills for hearing impaired students in the fourth grade of primary school in the Governorate of Dhofar in the Sultanate of Oman. The researcher conducted a pilot study to find out the most important language skills that need to be developed among students with hearing disabilities from the point of view of their teachers, in order to focus on their development through the proposed program. The researcher used the semi-experimental approach with one group. The research tools included a measure of language skills and the program applied with hearing-impaired students. The research sample was determined from all fourth-grade students (classes with hearing disability integration) and the number of students was (23) students, including (17) boys and (6) girls. The researcher also treated the study sample through a pre-measurement and a measurement after the application of the used program, and then a tracer measurement a month after the application of the program to verify the effectiveness of the applied program. The research reached results, the most important of which are: the existence of differences in statistical significance between the pre and post measurement scores in favor of the post measurement. This indicates the effectiveness of the program applied with hearing-impaired students and the continuation of the impact of the program through consecutive measurement. The research led to several recommendations, including: the need to pay attention to school theater, train students with hearing disabilities, use language communication skills through theater and its activities, and dramatize academic courses with hearing-impaired students to develop language communication and achieve cognitive comprehension in all academic courses and achieve attracting students' attention with these programs.